Workshop in a Box: Visual Demonstration of Small-Group Facilitation Techniques for Faculty Development - Tracy Fulton; Christian Burke; Katherine Hyland; Marieke Kruidering-Hall; Susan Masters (Association of American Medical Colleges, 2010)
Abstract Introduction This resource is designed for faculty who oversee the training of small-group facilitators for medical school courses. Included in this workshop is a DVD with two scripted, character-based dramatizations of small-group encounters, an instructors' guide, and structured written workshop materials. Methods The written materials provide guidance and structure for running a small-group facilitator training workshop using the DVD. Video clips on the DVD depict a group of learners engaged in a case discussion with one of two facilitators who have contrasting teaching styles. Results We have run several workshops for small-group facilitators using these materials. Three have been organized for small-group facilitators in the preclerkship curriculum, and one has been for residents in the School of Pharmacy. Preliminary data suggests that these materials are useful for faculty development, from both workshop leader and participant perspectives. In one workshop, 11 participants rated the usefulness of videos as a springboard for discussion 4.5 out of 5 on a Likert scale (5 = best), The overall quality of videos was rated 4.1. Self-efficacy improved in every category assessed, with the largest improvement in the following categories: managing overtalkative students (pre 2.64 post 3.60), differentiating between the "quiet student who is shy" and the "quiet student who has trouble with the material" (pre 1.82 post 2.8), and creating an atmosphere of active discussion among all students (pre 2.55 post 3.5). Discussion Course directors have found that these clips serve as useful tools for small-group facilitator training, making faculty development more consistent, realistic, and entertaining. Several additional faculty members have requested the video clips and plan to use them for small-group facilitator faculty development within their own discipline. Other faculty members have used these clips as case vignettes in the peer observation training. Though we have not collected data to support the effectiveness of the clips in these situations, anecdotally they have been very useful at demonstrating challenging and typical situations that would elicit both positive and corrective feedback.